PENGARUH PENGGUNAAN MEDIA “GOOGLE EARTH” BERBASIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN BERPIKIR SPASIAL SISWA PADA MATA PELAJARAN GEOGRAFI DI SMA N 5 BUKITTINGGI - Yurni Suasti; Zahra Miftahul Ain (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of google earth learning media on the spatial thinking ability of SMAN 5 Bukittinggi students. The research method used in this research is experimental method. Sampling was done by purposive sampling technique. The samples in this study were XI F7 students as the experimental class given the treatment of google earth application learning media and XI F6 class as the control class given the treatment of learning media in the form of maps. Data collection using pretest and posttest instruments in the form of multiple choice that has been tested for validity and reliability, as well as observation. The results of this study are the influence of google earth learning media on the spatial thinking ability of students in class XI F7 SMAN 5 Bukittinggi. The average posttest of the experimental class was 85.64 and the control class was 74.08. Data analysis using the Paired Sample T-test test from the calculated data obtained a significance level (Sig.) of 0.001 because the significance is smaller than 0.005 (0.001 <0.005), then Ho is rejected and Ha is accepted